PERAN PENDIDIKAN KARAKTER DALAM PENINGKATAN KUALITAS HIDUP DI TIGAKAMPUNG ADAT MASYARAKAT SUNDA - Esty Verawati; Marisha Adzani Poetri; Ichsan Fauzi Rachman (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This article was written using a literature study method by describing and comparing the characters of three traditional villages in Sundanese society, such as the Baduy Traditional Village, Naga Village and Cireundeu Traditional Village. The purpose of this article is to get an idea of how character education can improve the quality of life in Sundanese society in terms of their behavior, habits, and knowledge taught by their teachers. Sundanese people are famous for being a society that maintains noble values in their lives. Sundanese people still have strong nuances of ancestral traditions which become their character through culture, customs and advice. Education does not deserve to be called education if it ignores character formation, because knowledge without manners is useless. So the aim of the research from these three villages is to become an example of character education for children of the current millennial generation which has almost completely disappeared